The marketing-sales organizations as the way of internationalizing of the small and medium enterprises = Grupa marketingowo-sprzedażowa jako sposób umiędzynarodowienia działalności małych i średnich przedsiębiorstw - Piorunowska-Kokoszko, Joanna (Zielona Góra: Faculty of Economics and Management Press)
The internationalization is becoming a part of company's strategy, requiring some effort for getting its success. The present article is aimed at showing that joining the sale group is one of many ways of internationalizing activity for small and medium enterprises. The article presents the roles of sales group activity, its typical structure and opportunities and threats for its functioning.
Keywords: grupa sprzedażowa; internacjonalizacja; rozwój rynku; sales organization; internationalization; market development